Effectiveness of acceptance and commitment therapy (ACT) on sleep disorder and quality of life in mothers of children with learning disabilities (LD) - Kokabi, Ebrahim; Jahangiri, Mohammad Mehdi (Researcher Bulletin of Medical Sciences, 2026)
Objective: The impact of learning disabilities, struggles with life changes, and difficulties in communicating one’s needs has been documented in a wide range of health and social care evidence. Therefore, this study aimed to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on sleep disorder and quality of life in mothers of children with learning disabilities. Materials and Methods: The research approach is a quasi-experimental one, specifically a pre-test-post-test design with a control group. The research population consisted of all mothers with at least one child with learning disabilities who sought services at the Learning Disability Centers at District 2 of Tehran in the year 2023. A purposive sampling approach was employed, selecting 30 participants based on the inclusion and exclusion criteria for the study. These participants were then randomly divided into two groups: an experimental group and a control group. To gather data, the following instruments were used: Individual Clinical Characteristics Form, Pittsburgh Sleep Quality Index (PSQI). Multivariate Analysis of Covariance (MANCOVA) was used to analyze quantitative data using the SPSS statistical software, version 26. Results: The findings of the study revealed that after controlling for the effect of the pre-test scores, the difference in the pre-test-post-test scores between the two groups for the variables of sleep quality and quality of life was statistically significant. Additionally, the mean scores of the Acceptance and Commitment Therapy (ACT) group on the sleep quality and quality of life variables were also significantly higher than those of the control group (p < 0.05). Conclusion: Based on the research findings, it can be concluded that Acceptance and Commitment Therapy (ACT) is effective in improving sleep disorder and quality of life in mothers of children with learning disabilities.